The Implementation of Halal Product Guarantee in Indonesia and Malaysia: A Responsive Legal Theory Perspective - Achmad Fitrian (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The guarantee of product halal has a very important role in various aspects, especially for Muslim consumers. In Indonesia, the authority related to halal product assurance has indeed been regulated and guaranteed in various laws and regulations. This research focuses on the analysis of the comparison of halal product guarantee laws in Indonesia and Malaysia using an analytical framework with responsive legal theory. This research is a normative legal study with a conceptual, legislative, and comparative approach. The research results emphasize that the main difference in halal certification regulations is that in Indonesia, the important roles of BPJPH and MUI are highlighted, whereas in Malaysia, it is accommodated within a single institution, namely JAKIM. The implementation of halal certification in Malaysia is simpler because everything is regulated by a single body, whereas in Indonesia, halal certification is carried out by several institutions such as BPJPH, LPH, and MUI. From the perspective of responsive law theory, halal product assurance can be considered more responsive because it has involved the role of state governments in halal certification policies for micro, small, and medium enterprises, whereas in Indonesia, local governments have not yet been optimally involved in halal certification policies for micro, small, and medium enterprises. This research recommends that local governments in Indonesia should be involved in formulating regulations and policies to successfully implement halal product guarantees in Indonesia